Cytological and Biochemical Profile of Cerebrospinal Fluid from Meningitis Patients - Pandey, Pinky; Jha, Bharat; Shrestha, Anima (Annals of Clinical Chemistry and Laboratory Medicine, 2015)
BACKGROUND: The term Meningitis is used to describe an inflammatory infection of the membranes surrounding the brain and spinal cord, which occurs as either a primary disease or secondarily to disease in some other part of the body. The diagnosis is primarily confirmed by analyzing cerebrospinal fluid (CSF). Early diagnosis of the cause may be based on the cytological and biochemical parameters. Our objective was to determine the cytological and biochemical profile of CSF from meningitis patients. METHODS: In this cross sectional study, a total of 356 CSF specimens were collected from patients suspected of meningitis and processed microscopically and microbiologically by standard microbiological methods in Emergency Lab of Tribhuvan University Teaching Hospital (TUTH) Kathmandu, Nepal, over a period of six months, from March to August 2014 to determine cytological and biochemical parameters. RESULTS: Out of the 13 confirmed bacterial meningitis cases from 356 processed CSF samples, the mean value of total leukocytes count (TLC) was found to be 337.3 cells/mm3 with predominant neutrophils (73.8%). The mean value of glucose and protein was 28.8 mg/dL and 89.4 mg/dL respectively in the cases of bacterial meningitis. Among the three confirmed cases of fungal meningitis, the mean value of TLC was 11.7 cells/mm3 with lymphocytic predominance. In fungal meningitis glucose level was found to be normal (45.0 mg/dL) with slight increase in protein (48.7 mg/dL). CONCLUSIONS: Bacterial meningitis is generally characterized by increased TLC with predominance of neutrophils, decreased glucose and increased protein levels whereas fungal meningitis displays decreased TLC predominance of lymphocytes, normal or reduced glucose and slight increased protein level. DOI: http://dx.doi.org/10.3126/acclm.v1i1.12305 Ann. Clin. Chem. & Lab. Med. 1(1) 2015: 2-5